2012 IEEE 26th International Conference on Advanced Information Networking and Applications 2012
DOI: 10.1109/aina.2012.51
|View full text |Cite
|
Sign up to set email alerts
|

Clock Skew Based Client Device Identification in Cloud Environments

Abstract: Along with the growth of cloud computing and mobile devices, the importance of client device identity concern over cloud environment is emerging. To provide a lightweight yet reliable method for device identification, an application layer approach based on clock skew fingerprint is proposed. The developed experimental platform adapts AJAX technology to collect the timestamps of client devices in the cloud server during connection time, then calculate the clock skews of client devices. Few methods based on line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…However, as the result of piecewise minimum algorithm is not a straight line, we can not use it directly to approach one estimated skew value. Huang et al recently proposed a quick piecewise minimum algorithm (QPM) [9] to fit this requirement. QPM uses only minimum delays of the first segment and the last segment.…”
Section: A Skew Estimation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the result of piecewise minimum algorithm is not a straight line, we can not use it directly to approach one estimated skew value. Huang et al recently proposed a quick piecewise minimum algorithm (QPM) [9] to fit this requirement. QPM uses only minimum delays of the first segment and the last segment.…”
Section: A Skew Estimation Methodsmentioning
confidence: 99%
“…The goal of authentication servers is to verify the identity of users. When receiving the messages from web application, authentication server requests the corresponding personal data from the database server and exploits the identification technique mentioned in [9]. If the identity is valid, the authentication server grants the access of the web application.…”
Section: B Characteristics Of Clock Skewsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that both methods fail to give a correct estimation. It has also been reported that this kind of segmentation phenomena occurs when the route changes due to, for example, the sending device switching from a wired connection to a wireless one, or changing its mobile network relay base station [9]. Figure 2 (b) illustrates a somewhat overdone example.…”
Section: Introductionmentioning
confidence: 91%
“…As the widespread use of clock skew now ranges from cases of notebooks communicating inside a WLAN [4], [5] to smart phone applications accessing cloud services [7], [9], there is significant demand for an approach able to provide accurate estimations even to non-classical offset distributions. A well-known non-classical case is caused by time synchronization, e.g.…”
Section: Introductionmentioning
confidence: 99%